Breaking the mold: a brief review on the diagnostic and treatment approaches of mucormycosis - Mohanty, Aroop; Gupta, Pratima; Varshney, Saurabh; Kabi, Ankita; Angral, Sumeet (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Mucormycosis is a severe emerging angioinvasive fungal infection that occurs predominantly in immunocompromised individuals. The incidence of this disease seems to be increasing in recent years with the emergence of new causative agents and rise of the susceptible population. The present COVID-19 pandemic has seen an un-precented increase in the number of mucormycosis cases all over the world. It has emerged as one of the most common complication of COVID-19 leading to severe morality. Uncontrolled diabetes has been postulated to be the most common underlying disease in developing countries and hematological malignancies in case of the high-income countries. Besides diabetes, chronic renal failure and tuberculosis have also been predisposed in the Indian subcontinent. Rhino-cerebral form is mostly seen in diabetics whereas the pulmonary type is the most common presentation in patients with hematological malignancies and solid organ transplant. Diagnosis and treatment of this rapidly progressive disease is equally challenging. Microscopy and culture are the cornerstone for the diagnosis, but if assisted by imaging and molecular assays, it plays an important role in the correct and early identification of the causative agent. Successful management of mucormycosis is based on an integrated approach, including reversal or discontinuation of underlying risk factors, early administration of antifungal agents, and complete removal of infected tissue and use of various adjunctive therapies.